PENGARUH KOMPETENSI KARYAWAN DAN PEMBERIAN KOMPENSASI TERHADAP KINERJA KARYAWAN PADA KARYAWAN ALPHA HOTEL PEKANBARU - Siti Muthmainnah; Okta Karneli (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
This research is motivated by the importance of managing human resources in moving the company. In a company managing human resources well is one way to make employee performance improve. In achieving good performance, employees with high workforce are needed to anticipate opportunities and challenges in an increasingly competitive business environment. This research was conducted at the Alpha Hotel Pekanbaru company, Jalan Imam Munandar No. 17, Tangkerang Utara, Kec. Bukit Raya Pekkanbaru. The purpose of this study was to determine the level of employee performance at Alpha Hotel Pekanbaru. The sample of this study was taken as many as 76 respondents but due to the impact of Covid19, researchers only obtained respondents as many as 36 respondents using the census method. In this research the method used is descriptive and quantitative. Data obtained from interviews and questionnaires / questionnaires were then tested with statistics through the SPSS program. The analytical method used in this study is simple and multiple regression analysis, and by passing the validity test and the reliability test. In this study the results obtained are that Employee Competence has a positive and significant effect on Employee Performance, Giving Compensation has a positive and significant effect on Employee Performance and Employee Competence and Giving Compensation has a positive and significant effect on Employee Performance at Alpha Hotel Pekanbaru. Keywords: Employee Competence, Giving Compensation, and Employee Performance